Developing English Teaching Materials through Self-Vlogging Based on Speaking at Tertiary Level - Roswanti, Erni; Yasim, Sukmawati; Danial, Muhammad (Al-Lisan: Jurnal Bahasa, 2023)
This study aimed at developing English Teaching Materials through Self-Vlogging Based on Speaking, explaining the quality of English Teaching Materials through Self-Vlogging Based Speaking, and knowing the students’ perceptions of English Teaching Materials through Self-Vlogging Based Speaking. The sample for this research was students in the 3rd semester of the English Education Study Program, Faculty of Teacher Training and Education, Sulawesi Barat University. Researchers used the Research and Development method as the research method with a development model, namely the 4D model (Define, Design, Develop, Disseminate) which was simplified into a 3D model (Define, Design, Develop). The sampling technique used was Probability Sampling, namely Simple Random Sampling. The research instrument was a questionnaire that was used to assess research products on the research product validation sheet and was also used to determine students' perceptions of research products. The results of this study were (1) English Teaching Materials through Self-Vlogging Based for Speaking. (2) The media validation showed that the indicators' scores are in the category of ‘good’ and ‘very good’,(3) English Teaching Materials through Self-Vlogging Based for Speaking has positive perceptions from students as an English teaching material to help students practice speaking according to their interests.